The practicality of popular scientific books on Moraceae plant ethnobotany case study at KHDTK ULM - Nurul Wahdatun Nufus; Yudi Firmanul Arifin; Dharmono Dharmono (Master Program of Biology Education, Universitas Lambung Mangkurat, 2022)
Cultural heritage in an area that is unique is one step in preserving it so that it can be used as a source of learning based on local potential in contextual learning developed in popular scientific book teaching materials. This development research entitled